Gambaran Sumber Air dan Kejadian Diare di Kampung Tubir Kecamatan Paal II, Manado Periode Januari – Desember 2012 - Lagarense, Dhanny E. P.; Palandeng, Henry M. F.; Rombot, Dina V. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Background : Water is an essential component of the environment for human survival. Provision of clean water should beable to fulfill the needs of the people because the limited of fresh water will ease the spread of various diseases in thecommunity, one of which is diarrhea. Diarrhea remains one of the important public health issue. In Manado diarrhealdisease is a disease that causes a potential Extraordinary Events from 2009-2012. This study aims to obtain an overviewof the water source and the incidence of diarrhea in the Tubir village Paal II district of Manado. Methods : This study is adescriptive study using survey method to get an overview of the water source and the incidence of diarrhea in the Tubirvillage Paal II district of Manado which held for 3 months since October 2012 – January 2013. Population of this study wasall head of families and the number of samples obtained by using the Lemeshow formula 1997 is 100 head of families whofulfilled the inclusion criteria. Result and Conclusion: The result of the study of the water source found that the watersource used for daily needs the most is the river (52%), followed by plumbing water (PAM) (23%), the walled well (22%),and the least is not walled well. In order to obtain the needs of drinking water the large sourced (41%) from water refill,following the wells (23%), plumbing water (PAM) (21%), and the least is the river water (15%). From the results obtained,it was concluded that the incidence of diarrhea found 100 respondents, there were (74%) of respondents claimedto experience defecated with liquid fecal consistency > 3 times daily (diarrhea), while (26%) respondents had defecated <3 times daily (not diarrhea).Keywords: water source, diarrhea, diarrhea incidence